Comparison of the Outcomes of Total Endovascular Aortic Arch Repair Between Branched Endograft and Chimney Endograft Technique in Zone 0 Landing. (June 2022) - Kudo, Tomoaki; Kuratani, Toru; Shirakawa, Yukitoshi; Shimamura, Kazuo; Kin, Keiwa; Sakamoto, Tomohiko; Shijo, Takayuki; Watanabe, Yoshiki; Masada, Kenta; Sakaniwa, Ryoto; Sawa, Yoshiki
Purpose: Zone 0 landing in thoracic endovascular aortic repair (TEVAR) has recently gained increasing attention for the treatment of high-risk patients. The aim of this study was to compare the outcomes of total endovascular aortic arch repair between branched TEVAR (bTEVAR) and chimney TEVAR (cTEVAR) in the landing zone (LZ) 0. Materials and Methods: This was a single-center, retrospective, and observational cohort study. From January 2010 to March 2020, 40 patients (bTEVAR, n=25; cTEVAR, n=15; median age: 79 years) were enrolled in this study, with a median follow-up period of 4.1 years. These patients were considered unsuitable for open surgical treatment. Results: All procedures were successful and no cases of conversion to open repair were noted during the 30-day postoperative period. The 30-day mortality was 2.5% (n=1; bTEVAR [0 of 25, 0%] vs cTEVAR [1 of 15, 6.7%]; p=0.375), the perioperative stroke rate was 10.0% (n=4; bTEVAR [4 of 25, 16.0%] vs cTEVAR [0 of 15, 0%], p=0.278), and type 1a endoleak rate was 15.0% (n=6; bTEVAR [0 of 25, 0%] vs cTEVAR [6 of 15, 40.0%], p=0.001). The risk factor for stroke was atheroma grade of ≥2 in the brachiocephalic artery (p<0.001). The risk factor for type 1a endoleak was cTEVAR (p=0.001). The 8-year survival rate was 49.9%. The aorta-related death-free rate and aortic event-free rate at 8 years were 94.4% (bTEVAR: 95.5% vs cTEVAR: 93.3%, p=0.504) and 60.7% (bTEVAR: 70.7% vs cTEVAR: 40.0%, p=0.048), respectively. Conclusions: Total endovascular aortic arch repair using bTEVAR and cTEVAR is feasible for the treatment of aortic arch diseases in high-risk patients who are unsuitable for open surgery. However, as the rate of stroke is high, strict preoperative evaluation to prevent stroke is needed. No rupture of the aneurysm was observed in cTEVAR, but patients should be selected carefully because of the high incidence of type 1a endoleak.